Biomechanics of the sprint start - Harrison, D.; Comyns, T. (coachesinfo.com, 2009)
The short introduction is followed by a description of the of the sprint start, the purpose of the sprint start and its objectives. Finally the types of sprint start and the question are discussed: Which is the most effective type of sprint start?